Privacy Sanitization In Data Transmission (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Voice over Internet Protocol (VoIP) is a technology that  enables one to make and receive calls through the Internet  instead of using the traditional analog PSTN (Public  Switched Telephone Network) lines. Although, VoIP is  widely used technology but VoIP calls may also bring  security problems such as cyber crime issues. To solve the  security problems the contents of a VoIPsession should be  encrypted. Thispaper focuseson authenticationissues anduser ID detection as Security is an essential part of  human life depending on the voice signature of the  incoming VoIP calls. Our approach defines the speech  communication over the internet by detecting adversary to  avoid eavesdropping. HMM )Hidden Markov Model( is used to recognize the speaker on the basis of extracted  features. For this it first train the voice sample into wave  file. And then, to detect the speakers of encrypted speech  communications, we are proposing a new way of traffic  attacks using RTP (Realtime Transport Protocol). The  proposed traffic attacksarebasedonpackettiming informationonly. Thispaper shows that the proposed traffic analysis attacks can detect speakers of encrypted  speech communications with high detection rates based  on speech communication traces. While transmitting voice  over network naive tracing technique support for alternate  network to increase sanitization.
Keywords: VoIP; Speech Recognition; HMM; RTP; Si lence Suppression